Enhancing Sourdough Starter Using Ambon Banana Fermentation: A Comparative Study of Type I and Type III Starters Focusing on Lactic Acid Bacteria and Quality - Afianti, Linda Dwi; Saefi, Muhammad; Wahyudi, Didik (Journal of Biological Science and Education, 2025)
There are several main indicators that can be used to assess the quality of sourdough starter, namely pH, dough volume, and the presence and diversity of Lactic Acid Bacteria (LAB). Meanwhile, the addition of natural ingredients such as fermented Ambon bananas is considered to be able to improve the quality of sourdough starters, by increasing the number and diversity of LAB. This study is a comparative exploratory study that compares the quality of sourdough starters made with fermented Ambon bananas (Type III) and those made without Ambon bananas (Type I), and identifies the diversity of LAB in both. This study showed that all parameters are better in type III than in type I, where the pH is lower, the dough develops faster and has a larger volume, and the number of LAB is higher. Meanwhile, the LAB contained in Type III is more diverse (Lactobacillus pentosus, Lactobacillus plantarum, and Lactobacillus paraplantarum) compared to Type I, which only contains one isolate (Lactobacillus pentosus). Based on the results found, sourdough with the addition of Ambon banana fermentation can produce better starter quality and contains more diverse LAB, namely heterofermentative and homofermentative.Keywords: sourdough starter, fermented ambon banana fruit, lactic acid bacteria.